2012
DOI: 10.2165/11597410-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy and Safety of Fixed-Dose Amlodipine/Losartan and Losartan in Hypertensive Patients Inadequately Controlled with Losartan

Abstract: Registered at Clinicaltrials.gov as NCT00940680.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…More patients in the combination therapy groups responded to achieve the target BP compared with component monotherapies and with comparable adverse events (7275). Trials performed in South Korea and Japan have also shown beneficial effects of adding amlodipine to losartan and candesartan but these combinations of losartan/amlodipine and candesartan/amlodipine are not approved in the U.S. (7677). …”
Section: Efficacy Of Arbsmentioning
confidence: 99%
“…More patients in the combination therapy groups responded to achieve the target BP compared with component monotherapies and with comparable adverse events (7275). Trials performed in South Korea and Japan have also shown beneficial effects of adding amlodipine to losartan and candesartan but these combinations of losartan/amlodipine and candesartan/amlodipine are not approved in the U.S. (7677). …”
Section: Efficacy Of Arbsmentioning
confidence: 99%
“…Amlodipine is a calcium channel blocker (CCB) of the third generation dihydropyridine CCB group, used as monotherapy or in combination, for treatment of hypertension and angina [14]. Peripheral edema, particularly of the lower limbs, is a common adverse effect of dihydropyridine CCB.…”
Section: Introductionmentioning
confidence: 99%
“…Data were pooled from four randomized, double‐blind, clinical trials (three phase III and one phase II) that included essential hypertensive patients treated with amlodipine/losartan (HM‐ALOS‐201 [clinicaltrials.gov: NCT00942344]; HM‐ALOS‐301 [ClinicalTrials.gov: NCT00940667; HM‐ALOS‐302 [ClinicalTrials.gov: NCT00940680], HM‐ALOS‐303 [ClinicalTrials.gov: NCT01127217]) . In all studies, patients provided written informed consent, and study protocols were approved by the appropriate local ethical review boards of each study site.…”
Section: Methodsmentioning
confidence: 99%
“…COZAAR XQ (Merck & Co., Inc. Whitehouse Station, NJ) is an FDC therapy of amlodipine (5 mg, 10 mg) and losartan (50 mg, 100 mg) for the treatment of essential hypertension. Clinical trials have consistently shown that this FDC has resulted in significantly greater BP reduction compared with amlodipine or losartan monotherapy among patients with both essential hypertension and stage 2 hypertension . Losartan and amlodipine are frequently used as first‐line therapies in hypertensive patients, and other studies have also outlined the benefits of combining these two drugs…”
mentioning
confidence: 99%